Diurnal and seasonal migration of Weddell seals (Leptonychotes weddelli) in the region of Argentine Islands archipelago (Western Antarctic) - Dykyy, I. V.; Drongovska, M. O. (Ukrainian Antarctic Journal, 2015)
Material was collected during 11, 14 and 17 (season) Ukrainian Antarctic expeditions (2006 - 2007; 2009 - 2010 and 2011 - 2012) оn the territory archipelago Argentine islands (Western Antarctica). The archipelago total area occupies all nearby 3,5 km2. The archipelago serves original refugium for seals, owing to successful placing. Leptonychotes weddelli is widely distributed оn the territory archipelago. Studies Weddell seals migration was conducted using а method of photographing individual picture spots on the belly of the animal. Sex and age of the animals was determined bу generally accepted method. Results of re-registrations tagged seals, and photographic database ExtractCom pare program showed that most seals are kept within the archipelago of the winter and spring. However, the seal is often registered on the islands Winter , Skua, Galindez and Grotto in the winter-spring period. Some individuals were registered on the islands Leopard, Forge and Barchans. Animals are tied to specific places of rest, which occurs mainly а day and always соmе back to them after а night of hunting. In the lactation period, males usually located within the limits of 1-1.5 km from females. Females in lactation feeding in Penola Strait and the Cornice Channel, near the coastline of the island Winter leaving no pups for а long time. Previous studies show that at this time daily seals route do not exceed 5 km. But found that the greatest distance (over 25 km) can overcome some individuals, males and females so this species. Thus, we are discovered significantly phenomenon topical conservatism of the Weddell seals. Some animals are strongly tied to specific resting places that are well protected from wind and ocean waves. L. weddelli still numerous species, during December and January in the archipelago. Within Stella Creek strait always registered 5 - 7 individuals seals. Which are dominated bу males and young animals with last year. During February separate individuals of both sexes observed mainly in the area of lslands Barchans, Anagrams, Winter, Shelter and Rasmussen. We found that during the summer of seals migrates in а southerly direction outside the archipelago. ln particular, we registered animals on the island Barthelot, Darboux and Саре Perez, that was observed in winter near the Vernadsky base. In late summer and early autumn, most seals migrates in а northerly and north-westerly directions. Perhaps this is due to ice conditions. Specifically, we have registered the largest group of Weddell seals on the coast Cruls island in February 2007 - а total of 26 individuals of different sexes. We consider that daily migration Weddell seals associated with the presence in the water агеа the main food- krill. Seasonal migration of this species closely related to the ice conditions, availability of feed and reproductive period.